2016
DOI: 10.1002/2211-5463.12108
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an extracellular β‐glucosidase from Sporothrix schenckii

Abstract: An extracellular β‐glucosidase (http://www.chem.qmul.ac.uk/iubmb/enzyme/EC3/2/1/21.html), induced by cellulose in the mycelial form of human pathogen fungus Sporothrix schenckii, was purified to homogeneity using hydroxyapatite (HAp) adsorption chromatography in batch and Sephacryl S200‐HR size exclusion chromatography. The molecular mass of the purified enzyme was estimated to be 197 kDa by size exclusion chromatography with a subunit of 96.8 kDa determined by SDS/PAGE. The β‐glucosidase exhibited optimum cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
2
8
0
1
Order By: Relevance
“…The enhancement of exoglucanase activities in the presence of rice husk was in line with the report of Liu et al [118] in utilizing rice straw as a sole carbon source for Aspergillus fumigatus Z5. The OH strain maintained a lower level of enzyme production in the presence of glucose as a carbon source, suggesting a weak glucose catabolic repression activity, and similar glucose induction was observed in Sporothrix schenckii as well [119]. Moreover, this study shows similar lignocellulolytic production titers to other endophytic strains reported in the literature, i.e., Acremonium sp.…”
Section: Discussionsupporting
confidence: 84%
“…The enhancement of exoglucanase activities in the presence of rice husk was in line with the report of Liu et al [118] in utilizing rice straw as a sole carbon source for Aspergillus fumigatus Z5. The OH strain maintained a lower level of enzyme production in the presence of glucose as a carbon source, suggesting a weak glucose catabolic repression activity, and similar glucose induction was observed in Sporothrix schenckii as well [119]. Moreover, this study shows similar lignocellulolytic production titers to other endophytic strains reported in the literature, i.e., Acremonium sp.…”
Section: Discussionsupporting
confidence: 84%
“…A total of 308,372 β-glucosidase protein sequences had been identified in the NCBI protein database as of September 20, 2018. Among these protein sequences, most of the β-glucosidases were came from bacteria (282,519) (Chan et al 2016; Chen et al 2017; Sun et al 2018), followed by fungi (11,863) (Guo et al 2015; Hernandez-Guzman et al 2016). The β-glucosidases have the characteristics of cold adaptation (Crespim et al 2016; Ueda et al 2010), heat resistance (Leis et al 2018), salt tolerance (Lee et al 2015), glucose tolerance (Chamoli et al 2016; Chan et al 2016), and organic solvent tolerance (Thomas et al 2018) in extreme environments.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, β-glucosidases belonging to GH family 3 contain 600-900 amino acids in length with molecular weight of 65-90 kDa per subunit, but because these group of enzymes are usually glycosylated, their molecular mass ranges 110-130 kDa [44,157,158]. β-Glucosidase varies in quaternary structure arrangement, for example, monomeric [159], dimeric [160], trimeric [147], tetrameric [151] enzymes have been reported. Native molecular weight therefore may be higher than identified by SDS-PAGE [161].…”
Section: Molecular Weightmentioning
confidence: 99%
“…For example, β-glucosidase has been purified up to 9.47 fold from culture supernatant of Tolypocladium cylindrosporum Syzx4 using ammonium sulfate (75% saturation), dialysis, (DEAE)-cellulose column, and Sephadex G-100 column [68]. β-Glucosidase has also been purified from Aureobasidium pullulans using ammonium sulfate precipitation, CM Bio-Gel A agaraose, and sephacryl S-200 gel filtration chromatography up to 129 fold [80] and that from the human pathogenic fungus Sporothrix schenckii, was purified to homogeneity using hydroxyapatite (HAp) adsorption chromatography and Sephacryl S200-HR size exclusion chromatography [81]. Affinity chromatography methods such as Immobilized metal-affinity chromatography (IMAC) has been utilized for purification of recombinant enzymes containing short affinity tag of polyhistdine residues which show strong interactions with transition metal ions such as Ni 2+ immobilized in matrix [82].…”
Section: Purification Of β-Glucosidasementioning
confidence: 99%